2010
DOI: 10.3109/13550281003735717
|View full text |Cite
|
Sign up to set email alerts
|

Human immunodeficiency virus–associated cytomegalovirus infection with multiple small vessel cerebral infarcts in the setting of early immune reconstitution

Abstract: Cytomegalovirus (CMV) infection is an important cause of neurologic disease in the context of advanced human immunodeficiency virus (HIV) infection and is recognized as a cause of immune reconstitution inflammatory syndrome (IRIS) after initiation of highly active antiretroviral therapy (HAART). Central nervous system vasculitis secondary to CMV has only rarely been described in the context of HIV, despite the established ability of CMV to infect microvascular endothelial cells in the brain. However, we report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 22 publications
0
30
0
Order By: Relevance
“…The other one resulted from a CMV infection in a patient with a severe reduction in CD4+ cells and a high HI-viral load in plasma and CSF. This is noteworthy because so far Cytomegalovirus has only been associated with HIV and stroke in a few case series [26][27][28]. In another patient IgG antibodies against VZV were found in the CSF besides the presence of further vascular risk factors.…”
Section: Discussionmentioning
confidence: 92%
“…The other one resulted from a CMV infection in a patient with a severe reduction in CD4+ cells and a high HI-viral load in plasma and CSF. This is noteworthy because so far Cytomegalovirus has only been associated with HIV and stroke in a few case series [26][27][28]. In another patient IgG antibodies against VZV were found in the CSF besides the presence of further vascular risk factors.…”
Section: Discussionmentioning
confidence: 92%
“…3 A series of case reports showed that OIs [e.g., cryptococcal meningitis, cytomegalovirus (CMV), or Candida albicans infection] in HIV patients caused central nervous system vasculitis and may lead to stroke development. 3,1214 Although accumulating evidence suggests that OIs are associated with increased risk of incident stroke in HIV patients, few large-scale epidemiologic studies have investigated this association. Stroke management and prevention should include identification and prevention of specific stroke risk factors, particularly in high-risk populations.…”
Section: Introductionmentioning
confidence: 99%
“…CMV lumbosacral radiculitis has not been reported with IRIS. A case report suggests that CMV-IRIS could occur as a vasculitis causing multiple small infarcts [29]. Approximately 12% of HIV-1-associated VZV infections develop IRIS, which is more frequent than other OI-IRIS after the first 3 months of successful cART therapy, suggesting that VZV-IRIS immune responses are mediated by naïve CD4+ lymphocytes that emerge later after starting cART [30].…”
Section: Opportunistic Infections and Cns-irismentioning
confidence: 98%